2008
DOI: 10.1016/j.ygcen.2008.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and synaptic influences of serotonin on adult neurogenesis

Abstract: New neurons are incorporated into the adult brains of a variety of organisms, from humans and higher vertebrates, to non-vertebrates such as crustaceans. In virtually all of these systems serotonergic pathways appear to provide important regulatory influences over the machinery producing the new neurons. We have developed an in vitro preparation where adult neurogenesis can be maintained under highly controlled conditions, and are using this to test the influence of hormones on the production of neurons in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 44 publications
3
37
0
Order By: Relevance
“…As discussed later in this review, hormonally delivered serotonin has recently been implicated in the control of adult neurogenesis within several regions of the crustacean brain ( e.g. Benton et al 2008). …”
Section: Biogenic Amines and Their Derivativesmentioning
confidence: 98%
See 2 more Smart Citations
“…As discussed later in this review, hormonally delivered serotonin has recently been implicated in the control of adult neurogenesis within several regions of the crustacean brain ( e.g. Benton et al 2008). …”
Section: Biogenic Amines and Their Derivativesmentioning
confidence: 98%
“…Initially, Beltz and co-workers observed that the rate of neurogenesis in the lobster Homarus americanus brain decreased when serotonin was pharmacologically depleted using 5,7-dihydroxytryptamine Beltz et al 2001). Later, they demonstrated that the rate of neurogenesis in Homarus americanus was highly dependent on the serotonin concentration, with in vitro application of a low dose of serotonin (10 -10 M) to the brain eliciting a pronounced increase in neurogenesis and application of higher concentrations of serotonin resulting in a dosedependent decrease in neurogenesis (Benton et al 2008;Fig. 12).…”
Section: Modulatory Control Of Adult Neurogenesis By Serotoninmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoperiodic rhythmicity can be found in locomotory activity, size of the response of compound eye receptor potentials (ERGs), movement of pigment in the eyes and on the body (Aréchiga et al, 1993;FanjulMoles & Pietro-Sagredo, 2003), levels of serotonin in the brain (Benton et al, 2008;Wildt et al, 2003), and rate of neurogenesis in adult animals (Goergen et al, 2002). Many of these rhythms persist in conditions of constant darkness and are therefore under the control of endogenous circadian oscillators (Aréchiga et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Scatter plots did not indicate an effect of medication on odor identification; at the best in combination with co-morbidity identification is decreased. Although the mechanisms of serotonergic and dopaminergic effects on olfaction are insufficiently explored, one hypothetical mechanism might be pharmacological modulation of neurogenesis in the subventricular zone thus affecting the maturation of neural stem cells in the olfactory bulb into dopaminergic inhibitory interneurons (Benton et al 2008;Borta and Höglinger 2007). On the other hand, psychopharmacologic drugs might also act acutely and directly in the olfactory bulbs.…”
Section: Discussionmentioning
confidence: 99%